Constitutionalism and judicial constitutionalism in the Republic of Kazakhstan: origins and modernity - Nurmagambetov, A.M.; Nurmagambetova, S.B. (Bulletin of the Karaganda University “Law Series”, 2024)
The article provides a historical and legal analysis of the origin and formation of the institution of constitutionalism in the Republic of Kazakhstan, the relationship between constitutionalism and judicial constitutionalism, the role of the institution of constitutionalism in the legal regulation of public relations. The authors have step-by-step reviewed the Soviet experience in developing the concept of constitutionalism, and conduct a comparative analysis of the constitutional norms of the Soviet period to identify similarities and differences with the modern idea of constitutionalism. Despite the fact that the Constitution had the highest legal force in the USSR, it is not possible to speak about the existence of constitutionalism in the republics of the USSR, since the main values of constitutionalism are human rights and freedoms in conditions of reasonable state non-interference. Based on the study of many opinions of foreign and domestic researchers regarding the concept of constitutionalism, the authors have come to the following conclusions set out in this article. The concepts of “constitution” and “constitutionalism” should be distinguished. The latter is a broader concept and implies the formation of the concept of the constitution, ensuring the relationship between the constitution and law enforcement processes. The concept of judicial constitutionalism is derived from the concept of constitutionalism and is a set of decisions the constitutional control body on issues, as a rule, concerning the compliance of certain legislative norms with the provisions of the Constitution. A special role in the development of judicial constitutionalism in the Republic of Kazakhstan is played by the Constitutional Court of the Republic of Kazakhstan, whose activities are not limited to ensuring the protection of the foundations of the constitutional system, human and civil rights and freedoms.